The impact of crowdsourcing in product development: an exploratory study of Quirky based on the perspective of participants. Issue 1 (3rd April 2018) - Coelho, Denis A.; Nunes, Fábio; Vieira, Fátima Lanhoso
Abstract: This paper focuses on Quirky, a social product development (SPD) company, in order to explore the SPD phenomenon, as well as the self-assessed level of the experience quality arising from participation in SPD. The study investigates the perceived benefits to designers arising from their participation, the motivators of participation, as well as the participants' perception of SPD characteristics. It involved a focus session with seven industrial design engineering master students, and yielded results from which a questionnaire was developed within the study. The questionnaire was completed by voluntary participants (7 trained designers and 26 non-design trained participants) from the worldwide community of platform users of the selected SPD company. The questionnaire results suggest that the positive aspects of the SPD participants' experience include the interest caused by participation and motivation to earn money, as well as the perception of a wide range of ideas and contributions available in the SPD platform. Negative aspects of the participants' experience found in the analysis of the questionnaire data include high individual ratings for learning caused by participation as well as a keen awareness of too many unnecessary ideas in the SPD platform. The analysis also suggests that formally trained designers have some advantage in SPD participation compared to non-design trained participants. Finally, the results support the conclusion that the questionnaire respondents did not view SPD as detrimental to designers' future job prospects.